Geomatics engineering : a practical guide to project design - Ogaja, Clement A. (Boca Raton : CRC Press, 2011)
"Traditionally, land surveyors experience years of struggle as they encounter the complexities of project planning and design processes in the course of professional employment or practice. Giving beginners a l eg up and working professionals added experience, Geomatics Engineering : A Practical Guide to Project Design provides a practical guide to con temporary issues in geomatics professionalism, ethics, and design. It e xplores issues they face on a daily basis during the project design and the request for proposal process commonly used for soliciting professi onal geomatics engineering services. Organized into four sections, desi gned to develop critical thinking and problem solving, this book: refle cts the natural progression of project design considerations, including how the planning, information gathering, design, scheduling, cost esti mating, and proposal writing fit into the overall scheme of project des ign process; presents the details of contemporary issues such as standa rds and specifications, professional and ethical responsibilities, and policy, social, and environmental issues that are pertinent to geomatic s engineering projects; demonstrates the important considerations when planning or designing new projects; and focuses on the proposal develop ment process and shows how to put together a project cost estimate, inc luding estimating quantities and developing unit and lump-sum costs. Ba sed on experience of past projects, the book identifies priority areas of attention for planning new projects. Presenting the nuts and bolts o f geomatics projects, the author provides an understanding of professio nal and ethical responsibility, the impact of engineering solutions in a global and social context, as well as a host of other contemporary is sues such as budgetary and scheduling constraints."--Publisher's descri ption.
Project design process -- Standards and specifications -- Profession al and ethical responsibilities -- Policy, social, and environmental is sues -- Boundary surveys -- Control surveys -- Topographic surveys -- G IS application -- Estimating project costs -- Writing geomatics proposa ls.
Includes bibliographical references and index.
Keywords: Surveying; Geomatics; Project management; Geographic information systems